Graphene/Amorphous Carbon Restriction Structure for Stable and Long‐Lifespan Antimony Anode in Potassium‐Ion Batteries. Issue 26 (21st April 2020) - Yang, Xu; Zhang, Rongyu; Xu, Shifeng; Xu, Dan; Ma, Jia; Zhang, Zhongyu; Yang, Shu
Abstract: Sb‐based materials have attracted much attention owing to their ability to undergo a multi‐electron alloy reaction with K + . However, there are still the serious problems of volume change and aggregation of particles, which lead to rapid capacity fading and a limited lifespan. In this work, a graphene/amorphous carbon restriction structure is proposed, in which the amorphous carbon layer on the surface of Sb nanoparticles can protect the particles from pulverization, and the graphene can buffer the volume change of the material. In addition, the conductive network formed by the dual carbon structure effectively improves the rate performance of the material. Thus, the material delivers a high capacity of 550 mA h g −1 at 100 mA g −1, a rate capability of 370 mA h g −1 at 2000 mA g −1, and a long lifespan of 350 cycles without significant capacity fading. The dual carbon strategy proposed offers a reference for the design of high‐performance anode materials. Abstract : Under cover : A graphene/amorphous carbon restriction structure is designed for an Sb anode, in which the anode is protected from pulverization and aggregation, thus leading to the excellent stability and long lifespan of Sb in K‐ion batteries.